Pathogenic and genomic characterization of rabbit-sourced Pasteurella multocida serogroup F isolates recovered from dead rabbits with respiratory disease - Jinxiang Wang; Shikun Sun; Dongjin Chen; Chenfang Gao; Lei Sang; Xiping Xie (Microbiology Spectrum, 2024)
ABSTRACTPasteurella multocida serogroup F can infect a number of animals. However, the pathogenicity and genomic features of this serogroup are still largely unknown. In the present study, the pathogenicity and genomic sequences of 19 rabbit-sourced P. multocida serogroup F isolates were determined. The 19 isolates were highly pathogenic for rabbits causing severe pathologic lesions and high mortality in inoculated rabbits. Nevertheless, the pathologic lesions in rabbits caused by the 19 isolates were distinct from those caused by the previously reported high-virulent serogroup F strains J-4103 (rabbit), P-4218 (turkey), and C21724H3km7 (chicken). Moreover, the 19 isolates were avirulent to white feather broilers. The genomes of the 19 isolates were determined to understand the pathogenicity of these isolates. The finding of a number of functional genes in the 19 isolates by comparison with the low-virulent rabbit-sourced serogroup F strain s4 might contribute to the high virulence of these isolates. Notably, polymorphisms were determined in the lipopolysaccharide outer core biosynthetic genes natC and gatF among the serogroup F strains of different hosts. However, the sequences of natC and gatF from rabbit-sourced strains (except for SD11) were identical, which might be responsible for the host specific of the 19 isolates. The observations and findings in this study would be helpful for the understanding of the pathogenicity variation and host predilection of P. multocida.IMPORTANCEThe 19 rabbit-sourced Pasteurella multocida serogroup F isolates showing high virulence to rabbits were avirulent to the broilers. Notably, polymorphisms were determined in the lipopolysaccharide outer core biosynthetic genes natC and gatF among all serogroup F strains of different hosts. However, the sequences of natC and gatF from rabbit-sourced strains (except for SD11) were identical, which might be responsible for the host specific of the 19 isolates.